The solar community experience for the IEEE Region 9 - Palma Behnke, Rodrigo (2019)
Communities around the world are seeking ways to meet their energy requirements with clean, safe, resilient, and reliable energy systems. One way is through the use of solar energy at community level. This option has received much attention due to the following: i) reduction in the cost of the solar technologies; ii) novel control and communication approaches; iii) microgrids concepts; iv) co-construction approaches among project stakeholders. In fact, the main challenge of promoting energy solar solutions is to ensure sustainability. Efforts to define, promote, categorize, intervene, and assess the energy solar projects in communities are necessary but must incorporate multi-criteria approaches. With the support of IEEE and several institutions and volunteers, a cooperation network was created to share experiences and to promote sustainable solutions in communities of Latin America.